Cognitive-Reflective Motor Learning – Based Physical Education to Enhance Critical Thinking Abilities: Does RASCH Analysis Model show the Significant Evidence? - Bambang Abduljabar; Lutfi Nur; Ade Yulianto (Physical Education Theory and Methodology, 2025)
Background. This study addresses the need to enhance cognitive-reflective competencies in physical education, which often prioritizes mastering basic sports skills at the expense of cognitive development. In the information era, critical thinking is a crucial cognitive-reflective skill that must be fostered.